A Population‐based Study of Perinatal Infection Risk in Women with and without Systemic Lupus Erythematosus and their Infants. Issue 1 (1st December 2017) - Bender Ignacio, Rachel A.; Madison, Amy T.; Moshiri, Ata; Weiss, Noel S.; Mueller, Beth A.
Abstract: Background: Increased risk of adverse birth outcomes is well described in women with systemic lupus erythematosus (SLE), but risk of maternal or infant infection in the peripartum period has not been well studied. We conducted a population‐based cohort study of infection risk in women with and without SLE and their infants. Methods: Linked birth‐hospital discharge data identified 1297 deliveries to women with SLE and a 4:1 comparison cohort of deliveries to women without SLE in Washington State, 1987–2013. Maternal and infant infections during the first 30 days after delivery were identified. Relative risks (RR) and 95% confidence intervals (CI) were estimated. Results: Women with SLE were 1.7 times more likely (95% CI 1.4, 2.0) to have an infection during the birth hospitalisation and more likely to receive antibiotics during labour (RR 1.3, 95% CI 1.1, 1.5), though there was no increased risk of chorioamnionitis in women with SLE. Infants of women with SLE had an increased risk for an infection during the birth hospitalisation (RR 2.2, 95% CI 1.3, 3.5), although the size of the difference was smaller when adjusted for gestational age (RR 1.4, 95% CI 0.9, 2.1). Risks of neonatal infection, sepsis, receipt of antibiotics, and admission to neonatal intensive care were also increased, and were also attenuated after adjustment for gestational age. Conclusions: Women with SLE have an increased risk of peripartum infections and antibiotic exposure. Their neonates have a greater likelihood of infection, much of which is attributable to preterm birth.